Physiological Quality of Seeds of Eggplant, Pepper and Tomato Treated with Tiamethoxam, a Bioactivator Product - Meneghello, Géri Eduardo; da Silva, Andréia Almeida; Deuner, Cristiane; Soares Nogueira, Vanessa; Tunes Madruga, Lilian (Agrociencia Uruguay, 2016)
Considering the limited information on the effects of the bioactivator thiamethoxam and the potential benefits that this compound may provide in seed production, the aim of this study was to evaluate the influence of thiamethoxam in the physiological performance of the seeds of eggplant, sweet pepper and tomato. Seeds of three lots of each species were treated with six increasing doses of thiamethoxam (0; 0.2; 0.4; 0.6; 0.8 and 1.0 mL of product per 1000 seeds) and submitted to the standard germination test, first count of germination, cold test, accelerated aging test, total length of seedlings, and seedling emergence under glasshouse. The bioactivator had a positive effect on the analysed parameters, stimulating the physiological development of seeds, with variying intensities according to the lot. The average percentage of germination in the first count showed an increase of approximately 11 % for seed lots of eggplant, 13 % for sweet pepper, and 17 % for tomato seed lots. The dose of 0.6 mL per thousand seeds proved to be the most effective to increase the vigour of the seeds of the three species.